Formate-Dependent Microbial Conversion of CO2 and the Dominant Pathways of Methanogenesis in Production Water of High-temperature Oil Reservoirs Amended with Bicarbonate - Yang, Guang-Chao; Zhou, Lei; Mbadinga, Serge M.; Liu, Jin-Feng; Yang, Shi-Zhong; Gu, Ji-Dong; Mu, Bo-Zhong (Frontiers in Microbiology, 2016)
CO2 sequestration in deep-subsurface formations including oil reservoirs is a potential measure to reduce the CO2 concentration in the atmosphere. However, the fate of the CO2 and the ecological influences in Carbon Dioxide Capture and Storage (CDCS) facilities is not understood clearly. In the current study, the fate of CO2 (in bicarbonate form) (0~90 mM) with 10 mM of formate as electron donor and carbon source was investigated with high-temperature production water from oilfield in China. The isotope data showed that bicarbonate could be reduced to methane by methanogens and major pathway of methanogenesis could be syntrophic formate oxidation coupled with CO2 reduction and formate methanogenesis under the anaerobic conditions. The bicarbonate addition induced the shift of microbial community. Addition of bicarbonate and formate was associated with a decrease of Methanosarcinales, but promotion of Methanobacteriales in all treatments. Thermodesulfovibrio was the major group in all the samples and Thermacetogenium dominated in the high bicarbonate treatments. The results indicated that CO2 from CDCS could be transformed to methane and the possibility of microbial CO2 conversion for enhanced microbial energy recovery in oil reservoirs.